Echocardiographic screening of schoolchildren in American Samoa to detect rheumatic heart disease: a feasibility study - Shawn S Barnes; James Sim; James R Marrone; et al (Dove Medical Press, 2011)
Shawn S Barnes1 James Sim2 James R Marrone3 Venudhar D Reddy2 Darragh C O’Carroll1 Lauren Sumida1 Guliz Erdem21John A Burns School of Medicine, University of Hawaii, Honolulu, Hawaii, USA; 2Department of Pediatrics, John A Burns School of Medicine, University of Hawaii, Honolulu, Hawaii, USA; 3Department of Pediatrics, Lyndon Baines Johnson Tropical Medical Center, Pago Pago, American SamoaBackground: We report a practical and affordable pilot echocardiographic screening model for the detection of rheumatic heart disease (RHD) in Samoan children.Materials and methods: Following a brief training period, three medical students recruited and screened 58.3% (N = 140) of schoolchildren aged 7–18 years on the remote Pacific island of Ta’u, American Samoa, performing echocardiography with a SonoSite® portable ultrasound machine.Results: None of the echocardiographic images obtained showed significant abnormality consistent with RHD on their review by two pediatric cardiologists on Oahu, Hawaii.Conclusions: The implementation of echocardiographic screening in resource-poor regions with high rates of acute rheumatic fever and RHD, such as American Samoa, is feasible with limited training of personnel.Keywords: pediatric, RHD, Samoa, schoolchildren, screening